MODERN MECHANISMS FOR IMPROVING THE SPHERE OF MATERNAL AND CHILD HEALTH PROTECTION BASED ON THE CONCEPT OF JUVENILE BIOETHICS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This study provides a scientific-theoretical and practical analysis of modern mechanisms for improving maternal and child health protection based on the concept of juvenile bioethics. The work reveals the essence of the principles of juvenile bioethics, their place and significance in the system of maternal and child health protection. Issues regarding the application of the principles of child rights, human dignity, justice, autonomy, and non-harmfulness in medical and legal practice are also highlighted.